2012
DOI: 10.1177/1352458512438237
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological characteristics of tumefactive demyelinating lesions: follow-up study

Abstract: Although our demographic data were similar to formerly collected Turkish MS data, we found that the distribution of the patients' clinical course differed if there was an absence of primary progressive MS and that there was a lower frequency of secondary progressive MS cases in our group of patients. We believe that less frequent oligoclonal band positivity and the difference we witnessed in the clinical course of disease in our study groups suggest that there is a need for further studies to compare all the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
111
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 24 publications
11
111
4
3
Order By: Relevance
“…Unlike a previous report [10], no gender predilection was observed in our series, and a median age of 47 years at onset was older than that in most published series [9][10][11][12][13]. Sensory disorder, which is usually one of the most common clinical symptoms in previous studies [9,10,12], was only observed in two cases in our cohort, while other less common presentations including dizziness and brain stem signs (diplopia, dysphagia) were observed in our series.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Unlike a previous report [10], no gender predilection was observed in our series, and a median age of 47 years at onset was older than that in most published series [9][10][11][12][13]. Sensory disorder, which is usually one of the most common clinical symptoms in previous studies [9,10,12], was only observed in two cases in our cohort, while other less common presentations including dizziness and brain stem signs (diplopia, dysphagia) were observed in our series.…”
Section: Discussioncontrasting
confidence: 84%
“…Sensory disorder, which is usually one of the most common clinical symptoms in previous studies [9,10,12], was only observed in two cases in our cohort, while other less common presentations including dizziness and brain stem signs (diplopia, dysphagia) were observed in our series. In addition, the frequency of optic neuritis (ON) was a little higher than in previous reports [9][10][11][12].…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…При псевдотуморозном течении рассеянного склероза визуализируются контрастно-позитивные очаги демиелинизации, имеющие выраженный перифокаль-ный отек [20,21].…”
Section: дифференциальная диагностикаunclassified